Peningkatan Literasi Keuangan UMKM melalui Implementasi Program Pelatihan Kasir Pintar Berbasis Digital di Desa Sewaluh, Sidoarjo - Laila (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community engagement program was developed to enhance the financial literacy and digital capabilities of Micro, Small, and Medium Enterprises (UMKM) through training on the Kasir Pintar Pro application conducted in Sewaluh Village, Sukodono District, Sidoarjo Regency. The initiative was motivated by the low level of financial literacy and the limited application of digital technology in financial management within BUMDes Batik Sewaluh. The program consisted of three structured phases: (1) needs assessment and preparation, (2) theoretical instruction and hands-on training on digital cashier systems, and (3) post-training mentoring to ensure sustainable implementation. Evaluation employed pre-test and post-test assessments, field observation, and semi-structured interviews to determine the program’s effectiveness in improving digital financial literacy.Findings indicate a substantial improvement in participants’ understanding, with average knowledge scores rising from 60 to 88 (a 47% increase). The adoption of Kasir Pintar Pro enhanced bookkeeping efficiency by 75%, reduced data entry errors from 15% to 3%, and shortened financial reporting time from three hours to just thirty minutes daily. Furthermore, the system improved transparency and accountability through real-time online reporting accessible to BUMDes administrators.These outcomes confirm that practice-oriented training combined with intensive mentoring effectively strengthens institutional capacity and facilitates digital transformation at the village level. The results reinforce Ghezzi and Cavallo’s (2020) theory of digital adaptability as a key determinant of small business competitiveness and validate Badriyah and Hidayati’s (2025) assertion regarding the significance of continuous community mentoring for fostering sustainable local economic empowerment. Hence, the Kasir Pintar training serves as a replicable model of digital-based community empowerment applicable to rural UMKM.